Seacraft Names in Military Discourse - E. E. Golubkova; E. B. Kivileva (Дискурс профессиональной коммуникации, 2021)
The article analyses the process of meaning formation of names of warships in the military discourse with the aim of identifying conceptual mechanisms which underlie the naming of seacraft. The research constitutes part of the study in the field of cognitive linguistics and fills in the gap in the studies of metaphoric potential and cultural specificities of secondary names applied to artifacts (as big as warships) in British and American tradition. The results show that of all 1200 seacraft names, 700 units are originally zoomorphic common nouns transformed into proper names of seacraft with which they “share” and sometimes even exchange some of their basic or latent semantic characteristics. It was revealed that underlying mechanisms of meaning formation in seacraft nicknames are cognitive mechanisms of conceptual metaphor, focusing and defocusing. To describe them the methods of frame analysis and cognitive metaphoric modelling are employed. Metaphor in the paper is both the object and the tool of research. To support the analysis, the information about specific features of named objects and creatures is elicited from dictionaries and language corpora.